PENGARUH PROJECT BASED LEARNING DAN GAYA BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA - MUCHSINAN, KUN; PRASTITI, TRI DYAH; WAHYUNINGRUM, ENDANG (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This research was conducted using a quantitative approach with the aim of analyzing the effectiveness of the Project Based Learning (PjBL) model compared to the expository model. Additionally, the study also evaluated the significance of the interaction between the learning models and learning styles on students' critical thinking abilities and learning outcomes. The research method applied was a quasi-experiment using a 2 x 3 factorial design technique. The population involved all tenth-grade students in the academic year 2022/2023. Through random sampling, two classes were selected as the research sample. One class served as the experimental group implementing Project Based Learning, while the other class served as the control group with conventional (expository) learning. The data collection process was carried out using non-test instruments that included the variable